Health-related quality of life predicts length of hospital stay and survival rates for pediatric patients receiving allogeneic hematopoietic cell transplantation. - Liu, Ying-Mei; Jaing, Tang-Her; Wen, Yu-Chuan; Chen, Shih-Hsiang; Weng, Pei-Yin; Lin, Lin; Wu, Chia-Ling (Quality of Life Research, 2021)
Purpose: We examined the association between health-related quality of life (HRQoL) of pediatric patients during hospitalization for allogeneic hematopoietic cell transplantation (HCT) and length of hospital stay, and 1-year survival.Methods: Primary family caregivers were proxy-assessors for the Pediatric Quality of Life (PedsQL) Stem Cell Transplant Module at three time points: 5-days pre-HCT (T0); 14-days post-HCT (engraftment, T1); and 1-week before hospital discharge (T2). Cox regression analyses determined predictors of the overall 1-year survival after allogeneic HCT.Results: Thirty-nine eligible caregivers completed all assessments. The mean age of the pediatric patients was 9.07 years (SD = 5.2). PedsQL Stem Cell Transplant Module scores decreased from 71.33 (SD = 13.26) at T0 to 55.41(SD = 13.05) at T1 (p < 0.001) and increased to 68.46 (SD = 13.97) at T2 (p < 0.001). There was no significant difference between scores at T0 and T2. Longer length of hospital stay was associated with children who were younger and had greater relative changes in scores on the caregiver-proxy PedsQL Stem Cell Transplant Module from T0 to T1. PedsQL Stem Cell Transplant Module scores ≥ 58.07 at T2 were associated with higher 1-year survival rates (Hazard Ratio = 0.12, 95% Confidence Interval = 0.02-0.78; p = 0.03).Conclusion: Our findings suggest that assessment of HRQoL during early HCT can add prognostic value beyond demographic and HCT factors. Understanding the HRQoL status during hospitalization for HCT could help identify pediatric patients with low prospects of 1-year survival in order to provide support interventions to improve HRQoL and survival rates.